Overeducation among immigrants in Sweden: Incidence, wage effects and state dependence - Pernilla Andersson Joona; Nabanita Datta Gupta; Eskil Wademsjö (IZA Journal of Migration, 2014)
The utilization and reward of the human capital of immigrants in the labor market of the host country has been studied extensively. Using Swedish register data from 2001 - 2008, we extend the immigrant educational mismatch literature by analyzing incidence, wage effects and state dependence in overeducation among natives and immigrants. In line with previous research we find a higher incidence and a lower return to overeducation among immigrants indicating that immigrants lose more from being overeducated. We find a high degree of state dependence in overeducation both among natives and immigrants, but considerably higher among immigrants.
Keywords: J61; I21; J24; J31; F22; 330; Educational mismatch; Immigrants; State dependence; Wages